1995
DOI: 10.1364/ol.20.001821
|View full text |Cite
|
Sign up to set email alerts
|

Z-scan measurement technique for non-Gaussian beams and arbitrary sample thicknesses

Abstract: We demonstrate a new Z-scan measurement technique that permits the use of non-Gaussian beams and thick, as well as thin, samples. We expect that this technique will make possible the measurement of optical nonlinearities by the use of lasers that previously would have been unsuitable for this purpose, because of either inadequate beam quality or inadequate power. Another advantage of this technique is that it does not require detailed knowledge of the temporal characteristics of the laser pulse that is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 9 publications
0
16
0
1
Order By: Relevance
“…Still, a well characterized and clean input beam profile is required for precise measurements [20]. Bridges et al have demonstrated a technique which partially relaxes the stringent beam shape requirement by measuring the nonlinearity of the sample relative to a reference sample [26]. The key mechanism of the Z-scan technique is to measure the SPM-induced phase shift via its effect on the far-field diffraction pattern.…”
Section: The Z-scan and The Spectral Re-shaping Techniquementioning
confidence: 99%
“…Still, a well characterized and clean input beam profile is required for precise measurements [20]. Bridges et al have demonstrated a technique which partially relaxes the stringent beam shape requirement by measuring the nonlinearity of the sample relative to a reference sample [26]. The key mechanism of the Z-scan technique is to measure the SPM-induced phase shift via its effect on the far-field diffraction pattern.…”
Section: The Z-scan and The Spectral Re-shaping Techniquementioning
confidence: 99%
“…When the applicability of the thin lens regimel casts some doubt, more complex methods of problem solution are used based on regimeling of the profile of the light beam transmitted through the nonlinear medium [9,10]. It has been demonstrated that non-Gaussian beams can also be used in these experiments [11].…”
Section: Introductionmentioning
confidence: 99%
“…20 In this method one first makes a Z-scan measurement of a reference sample, the nonlinear optical parameters of which are known. Then the experiment is repeated for a test sample with the input power adjusted to get the same normalized peak-to-valley transmittance as that for the reference sample.…”
Section: Introductionmentioning
confidence: 99%